Effects of Transcranial Direct Current Stimulation on Cognition, Mood, Pain, and Fatigue in Multiple Sclerosis: A Systematic Review and Meta-Analysis - Hsu, Wan-Yu; Cheng, Chia-Hsiung; Zanto, Theodore P.; Gazzaley, Adam; Bove, Riley M. (Frontiers in Neurology, 2021)
Background: The study aimed to evaluate the effects of transcranial direct current stimulation (tDCS) on cognition, mood disturbance, pain and fatigue in people with multiple sclerosis (PwMS). Methods: A literature search was performed on articles published between January 1990 and May 2020 in Pubmed, Medline and Web of Science using the following keywords and their abbreviation in combinations: multiple sclerosis and transcranial direct current stimulation. Mean effect size (ES) and 95% confidence interval were calculated for each domain of interest. Results: Seventeen articles with a total of 383 PwMS were included in this analysis. For cognition, a strong effect size was found for the trial administering the Symbol Digit Modalities Test (ES: 1.15), whereas trials applying the Attention Network Test showed a negative effect size of -0.49. Moderate to strong effect sizes were observed for mood disturbance (mean ES: 0.92), pain (mean ES: 0.59) and fatigue (mean ES: 0.60). Further subgroup analyses for MS-related fatigue showed that both high and low intensities of stimulation lead to nearly the same degree of favorable effects. More pronounced effects were observed in studies administering the Fatigue Severity Scale compared with studies using other fatigue measures such as the Modified Fatigue Impact Scale. Conclusion: These results provide preliminary evidence that tDCS has a favorable effect on cognitive processing speed, mood disturbance, pain and fatigue in MS. However, the effects on cognition and fatigue vary based on the specific assessment used.